SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN KELAYAKAN BISNIS MENERAPKAN SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) - diana, diana (Universitas Bina Darma, 2016)
Abstract: Criteria for the feasibility study in this research is the aspect of finance and economics, consists of six criteria: Payback Period, Net Present Value, Average Rate of Return, Internal Rate of Return, Profibility Index. Benefits of this feasibility study to determine which businesses are worth proceed or not proceed. The method applied is Simple Multi-Attribute Rating Technique (SMART) was chosen because of its simplicity in calculation process, thus simplifying construction of the system. Step system development is the waterfall method, consisting of 1) Analysis of software requirements, 2) Design, 3) Preparation Program Code and 4) Testing. This research resulted in a decision support system in order to determine the feasibility of a business by applying Simple Multi-Attribute Rating Technique (SMART). In the testing phase obtained by the fact that businesses are recommended to change depending on the value of the weight of the criteria entered by the user. Keyword: Decision Support Sysem, Busines Feasibility Study, SMART